2017
DOI: 10.21837/pmjournal.v15.i6.252
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Sustainable Wellbeing Indicators for Human Interrelationships With the Environment

Abstract: The environment should appear not only as a commodity to humans but as an inspiring source that appeals to humans' ethical ability. In Malaysia, studies concerning factors influencing pro-environmental behaviours are vast. However, studies on interrelationships between humans and the contextual surroundings are scarce. Towards achieving sustainable well-being, it is undoubtedly important for humans to have conforming emotions, behaviours, cognitions and motivations towards the environment. This study intends t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Human interrelationship dimensions with the environment refers to areas where human interrelationship variables with the environment are manifested (Bakar et al, 2017). Therefore, the study area was chosen based on similar settings or situations in which students and campus environment interactions take place.…”
Section: Study Areamentioning
confidence: 99%
“…Human interrelationship dimensions with the environment refers to areas where human interrelationship variables with the environment are manifested (Bakar et al, 2017). Therefore, the study area was chosen based on similar settings or situations in which students and campus environment interactions take place.…”
Section: Study Areamentioning
confidence: 99%
“…Measures of individuals functionality and contributions to their social and environmental contexts that in turn influence the well-being of the individuals is known as Human Interdependence [HI] (Abu Bakar et al, 2019a;2019b;2019c;Abu Bakar et al, 2020a;2020b;2020c). Detailed studies on HI found that HI predicts 70% of Subjective Well-Being, suggesting that a huge source of individual well-being exists in the course of imparting well-being to social and environment surroundings (Abu Bakar et al, 2015;2016a;2016b;2017a;2017b;2017c;2017d;2017e;2017f;2018). This paper focuses on Human Interdependence with the Environment [HIE].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human Interdependence [HI] measures the contributions and functionality of individuals in their social and environmental contexts that in turn influence the well-being of the individuals (Abu Bakar et al, 2019a;2019b;2019c;Abu Bakar et al, 2020a;2020b;2020c). Thorough studies on HI discovered that HI contributes to 70% of Subjective Well-Being, suggesting that that imparting wellbeing to social and environmental surroundings is a huge source of individual well-being (Abu Bakar et al, 2015;2016a;2016b;2017a;2017b;2017c;2017d;2017e;2017f;2018). This paper focuses on Human Interdependence with the Environment [HIE].…”
Section: Literature Reviewmentioning
confidence: 99%